A cultivable acoel species from the Mediterranean, Aphanostoma pisae sp. nov. (Acoela, Acoelomorpha) - Zauchner, Thomas; Salvenmoser, Willi; Egger, Bernhard (Zootaxa, 2015)
Aphanostoma pisae sp. nov. is an interstitial acoel found at the coast of the Liguric Sea in Pisa (Tuscany, Italy). It belongs to the large family Isodiametridae, characterised by a male copulatory organ with a cylindrical shape and non-anastomising longitudinal muscle fibers. It is the first recognised species of Aphanostoma in the Mediterranean and it can occur in great abundance at its type locality (several hundred specimens in a spoonful of sand). A. pisae has been cultured in the laboratory for several years with diatoms for food. The embryonic development lasts for just under two days at 20 °C. We provide a description of the new species using live observations, light and electron microscopy of sagittal sections and stainings of the filamentous actin and the serotonergic nervous system, and we discuss and update the genus diagnoses of the genera Aphanostoma and Praeconvoluta.